Coping Mechanism of Women as Solo Parents of Children with Autism - Foronda, Carla G. (Review of Women's Studies; Vol 10 No 1-2 (2000): Review of Women's Studies Volume X, Numbers 1-2 (January-December 2000), 2001)
This study describes the coping experience of single parents of children with autism in relation to family, belief, and social factors. Sixteen single women parents of children with autism from Manila and Laguna participated in the research. The main research instruments utilized included a questionnaire, interview schedule, and observation log. Quantitative and qualitative data were analyzed and integrated into a final report.